Alkisti Efthymiou in Conversation with Athena Athanasiou: Spectral Publics and Antifascist Eventualities - Efthymiou, Alkisti; Athanasiou, Athena (Identities: Journal for Politics, Gender and Culture, 2019)
This text is a conversation between Athena Athanasiou and Alkisti Efthymiou, drawing from Athena Athanasiou’s new book, Agonistic Mourning: Political Dissidence and the Women in Black (Edinburgh University Press, 2017). The conversation discusses the critical potency of collective subjectivities such as the Women in Black and expands on issues that include political agency, vulnerability in resistance, spacing appearance, performing public mourning, or the traveling of social movements, associating them with contemporary feminist and antifascist urgencies. Central to the text is the concept of non-sovereign agonism, a form of political agency that addresses (or takes into account) the dispossessed quality of subjectivity and pays attention to the relationality through which we are constituted as subjects. Author(s): Alkisti Efthymiou and Athena Athanasiou Title (English): Alkisti Efthymiou in Conversation with Athena Athanasiou: Spectral Publics and Antifascist Eventualities Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 16, No. 1-2 (Summer - Winter 2019) Publisher: Institute of Social Sciences and Humanities - Skopje Page Range: 102-113 Page Count: 12 Citation (English): Alkisti Efthymiou and Athena Athanasiou, “Alkisti Efthymiou in Conversation with Athena Athanasiou: Spectral Publics and Antifascist Eventualities,” Identities: Journal for Politics, Gender and Culture, Vol. 16, No. 1-2 (Summer - Winter 2019): 102-113.